Elementar - Männer in der pädagogischen Arbeit mit Kindern - Aigner, Josef Christian; Rohrmann, Tim (Verlag Barbara Budrich, 2012)
The demand for more men as pre-school teachers in day-care centres is becoming clearer and clearer For this reason, the Austrian research project "Elementar" has comprehensively investigated the situation of male pre-school teachers and carers in the elementary field in a unique study. The diverse results emphasise the opportunities associated with the participation of men, but also call for a critical and differentiated examination of gender issues in the elementary field. Pupils, trainees and teachers working in practice were interviewed using quantitative and qualitative methods. Male trainees and skilled workers were surveyed in a full survey. The results were evaluated using statistical methods and qualitative content analyses. For the first time, biographical backgrounds and identities of male pre-school teachers were also examined psychoanalytically. On the basis of their results, the authors formulate concrete calls for action for research, practice and politics.